Aluminium, gallium, and molybdenum toxicity to the tropical marine microalga Isochrysis galbana. (9th June 2015) - Trenfield, Melanie A.; van Dam, Joost W.; Harford, Andrew J.; Parry, David; Streten, Claire; Gibb, Karen; van Dam, Rick A.
Abstract: There is a shortage of established chronic toxicity test methods for assessing the toxicity of contaminants to tropical marine organisms. The authors tested the suitability of the tropical microalga Isochrysis galbana for use in routine ecotoxicology and assessed the effects of 72‐h exposures to copper (Cu, a reference toxicant), aluminium (Al), gallium (Ga), and molybdenum (Mo), key metals of alumina refinery discharge, on the growth of I. galbana at 3 temperatures: 24 °C, 28 °C, and 31 °C. The sensitivity of both I. galbana and the test method was validated by the response to Cu exposure, with 10% and 50% effect concentrations (EC10 and EC50) of 2.5 μg/L and 18 μg/L, respectively. The EC10 and EC50 values for total Al at 28 °C were 640 μg/L and 3045 μg/L, respectively. The toxicity of both Cu and Al at 24 °C and 31 °C was similar to that at 28 °C. There was no measurable toxicity from dissolved Ga exposures of up to 6000 μg/L or exposures to dissolved Mo of up to 9500 μg/L. Solubility limits at 28 °C for the dissolved fractions (<10 kDa) of Al, Ga, and Mo were approximately 650 μg/L Al, >7000 μg/L Ga, and >6000 μg/L Mo. In test solutions containing >650 μg/L total Al, dissolved and precipitated forms of Al were present, with precipitated Al becoming more dominant as total Al increased. The test method proved suitable for routine ecotoxicology, with I. galbana showing sensitivity to Cu but Al, Ga, and Mo exhibiting little to no toxicity to this species. Environ Toxicol Chem 2015;34:1833–1840. © 2015 SETAC